Teachers' Attitudes towards the Use of Brain-Based Learning Theory Principles "A Field Study on a Sample of Teachers of the First Cycle of Basic Education in Lattakia City" - اسكندر, حسين; وليد حمادة; احمد خليفة (Latakia University Journal - Arts and Humanities Sciences Series, 2024)
The current research aims to explore the attitudes of primary school teachers in Latakia city towards the use of brain-based learning principles, and the relationship of these attitudes with the teachers' academic qualifications and years of experience. The study utilized a descriptive methodology, with a questionnaire developed by the researcher as the research tool, and included a sample of (280) male and female teachers from the first cycle of basic education in the schools of Latakia. The research results indicate that the individuals in the sample possess neutral attitudes towards the use of brain-based learning principles. Additionally, the number of years of experience of the teacher influences their attitudes towards the use of brain-based learning principles in favor of teachers with more experience. However, the academic qualifications of the teacher did not affect their attitudes towards the use of brain-based learning principles.